Genetic divergence study in linseed (Linum usitatissimum L.) through D2 and principal component analysis: GENETIC DIVERGENCE STUDY IN LINSEED THROUGH D2 AND PRINCIPAL COMPONENT ANALYSIS - SHWETA KUMARI; NEHA RANI; AWADHESH K PAL; RAM BALAK PRASAD NIRALA (Journal of Oilseeds Research, 2018)
Genetic diversity among thirty one linseed genotypes was studied using D2 analysis and principal component analysis (PCA) to efficiently utilize the breeding potential of linseed genotype for improving the yield. On the basis of D² analysis, these genotypes were grouped into six divergent clusters in which cluster I was largest with 12 genotypes followed by cluster II and cluster V. The resultsshowed the highest contribution oflinolenic acid towards genetic diversity. However, inter cluster D2 value was found to be highest between cluster II and VI followed by V and VI. On the basis of cluster mean, the genotypes of cluster IV were characterized by the highest cluster mean for seed yield per plant and cluster II for oil content and linolenic acid. Principal component analysis distributed all the variables into six principal components accounting for 88.17 per cent of the total variation suggesting the presence of considerable genetic diversity among the genotypes for different characters. Hence, the information obtained can be utilized in selecting diverse parents to get better segregants in linseed breeding programmes.